O Programa Nacional de Alimentação Escolar como promotor do desenvolvimento rural sustentável e da segurança alimentar e nutricional em Marechal Cândido Rondon - PR - Garcia, Jaciara Reis Nogueira (2018)
The definition of Sustainable Development is related to the involvement of two concepts: development and sustainability. It can be pointed out that development occurs only when there is a redefinition of the connexion between society and nature. Thus, the relation between Public School of Food Policy and the idea of development was built on such concepts. The National School Feeding Program (NSFP) is shown as a possibility that allows the transition from concept to action. An instrument that can provide actions where several social actors can take part of their transformation of reality in a conscious way as well as establish new values. NSFP legislation emphasizes the importance of actions that aimed at promoting Food and Nutrition Security, mainly as a strategy to achieve Food Sovereignty and Human Right to an adequate diet. So, it is observed that both Food and Nutritional Security (FNS) and Sustainable Rural Development (SRD) are intertwined. Little has been highlighted about actions and reactions caused by the deployment and execution of NSFP as formers of an integrated environment for local diet and nutritional security policy. Thereby, this paper aims at analyzing NSFP actions that may or may not characterize it as an inducer of both Sustainable Rural Development and FNS guarantee. It is based on a case study in Marechal Cândido Rondon-PR, whose goals are on the results to fulfill this program in the city. Therefore, an exploratory and documentary research was carried out concerning the program deployment in this municipality as well as the application of questionnaires and interviews with several social actors that took part of it, such as farmers, school cooks, and managers of Municipal School Feeding. The results indicate that NSFP plays a fundamental role as a promoter of SRD, that its legislation enforcement is essential to guarantee FNS and improve those people's living quality. Finally, it is concluded that NSFPs an important instrument that makes feasible familiar agriculture valuation as well as the process of keeping man in the countryside, recovery of local feeding habits, healthy and organic food production policies, education and environmental protection policies and, mostly, adequate nutritional care for the school population.